Interaction of some selected Trace elements with Thyroid hormones in patients with Goiter in Ibadan, Nigeria (2014)
Trace elements influence hormones at different levels of action, including hormone secretion, activity and binding to target tissue. Thyroid hormones also influence the metabolism of some essential trace elements. There is paucity of knowledge on the interaction of some trace elements in goiter development in the study environment. This study was carried out to determine the levels of selenium, copper, and zinc and their correlation with free triiodothyronine (fT3), free thyroxine (fT4), and Thyroid Stimulating Hormone (TSH) in patients with goiter in Ibadan. Sixty randomly selected participants who agreed to participate by signing the consent form following due explanation of the purpose of the study, were recruited. They comprised of 30 female patients (19 hyperthyroid and 11 euthyroid) attending the Nuclear Medicine and Surgery clinics of the University College Hospital, Ibadan, and 30 apparently healthy women as controls. Serum zinc, copper and selenium were determined by atomic absorption spectrophotometery and fT3, fT4 and TSH by ELISA. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) soft version 20.0 and data were expressed as mean and Standard Error of Mean (SEM). Results showed that hyperthyroid goiter patients had significantly lower levels of Selenium (0.9±0.027 vs. 4.00±0.02 µg/dl), Zinc (70.56±1.46 vs. 73.88±2.05 µg/dl) and Copper (85.23±5.09 vs. 123.11±1.80 µg/dl) compared with the controls (p<0.05). For euthyroid goiter, a significant positive correlation was found between FT3 with copper and selenium (p<0.05, r=0.46), (p<0.05, r=0.80) respectively; and positive correlation (p<0.05, r=0.46) between Zinc and TSH in the hyperthyroid group. Diets and/or supplementations rich in Selenium, Copper and Zinc may reduce the development of certain goiters.